2022
DOI: 10.48550/arxiv.2204.04563
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Production of Higgs boson in association with a pair of fermions in the presence of a circularly polarized laser field

Abstract: In the centre of mass frame, we have investigated the process of Higgs production in association with a pair of fermions, e + e − → f f H, at the leading order inside an intense electromagnetic field with circular polarization. Our analytical calculations are based on the Narrow Width Approximation (NWA), which is valid in the leading order. We have considered only the initial particles inside the laser field as a first step. In the second part, we have embedded both initial and final particles in the laser fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…In 2014, Sarah Muller et al [11,12] conducted pioneering research on Higgs boson production and various particle physics processes in lepton collisions boosted by a laser field. Recently, another group of authors has also studied different physical processes in the SM and beyond [13][14][15][16][17], including charged Higgs boson production [18][19][20]. A review of such contributions in strong field quantum electrodynamics (QED) can be found in [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…In 2014, Sarah Muller et al [11,12] conducted pioneering research on Higgs boson production and various particle physics processes in lepton collisions boosted by a laser field. Recently, another group of authors has also studied different physical processes in the SM and beyond [13][14][15][16][17], including charged Higgs boson production [18][19][20]. A review of such contributions in strong field quantum electrodynamics (QED) can be found in [21,22].…”
Section: Introductionmentioning
confidence: 99%